Software engineering theory and practice - Pfleeger, Shari Lawrence (Pearson Prentice Hall, 2006)
This book is also suitable for a graduate course offering an introduction to software engineering concepts concept ang practices, or for practitioners wishing to expand their knowledge of the subject. In particular, Chapters 12,13 and 14 present thoughtprovoking material designed to interest graduate students in current research topics.